2006
DOI: 10.1002/eji.200535387
|View full text |Cite
|
Sign up to set email alerts
|

TCR‐independent cytokine stimulation induces non‐MHC‐restricted T cell activity and is negatively regulated by HLA class I

Abstract: Recent evidence suggests that the functional status of T cells activated independently from their TCR differs substantially from classical MHC-restricted T cells. Here, we show that TCR-independent, short-term stimulation via the common c-chain of the IL-2/IL-15 receptor induces non-MHC-restricted cytotoxicity and sustained cytokine secretion in purified CD4 + or CD8 + T cells. NK-like cytotoxicity is directed against MHC class Inegative targets and can be inhibited by classical and non-classical HLA class I m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
(57 reference statements)
1
18
0
Order By: Relevance
“…Our results, therefore, could be interpreted in different aspects: lesions (and cannot be compared to the primary tumor) and this has to be taken into account when designing interventional trials. In detail, the comparison of the NKspecific marker NKp46 with CD56 revealed that NK-cell quantities cannot be estimated from staining with CD56 alone (19)(20)(21). For other gastrointestinal cancers, the available data is ambiguous due to the use of CD56 in stainings.…”
Section: Discussionmentioning
confidence: 99%
“…Our results, therefore, could be interpreted in different aspects: lesions (and cannot be compared to the primary tumor) and this has to be taken into account when designing interventional trials. In detail, the comparison of the NKspecific marker NKp46 with CD56 revealed that NK-cell quantities cannot be estimated from staining with CD56 alone (19)(20)(21). For other gastrointestinal cancers, the available data is ambiguous due to the use of CD56 in stainings.…”
Section: Discussionmentioning
confidence: 99%
“…There are two chief schools of thought: bystander T cell activation results in effector functions (5,7,12,13,48), which may be damaging (in the case of immunopathology) or helpful (contributing to resolution of infection (49 -52)); alternatively, bystander T cell activation simply results in apoptosis and attrition of the existing repertoire to make way for the newly expanded, directly activated T cells. There is considerable evidence that bystander T cells undergo attrition.…”
Section: Discussionmentioning
confidence: 99%
“…There is much evidence that cytokine stimulation (5)(6)(7)(8)(9)(10)(11)(12)(13) or cross-linking of certain membrane-bound receptors (14,15) is capable of activating T cells in the absence of TCR ligation. Few studies, however, address whether physiological levels of these cytokines produced during an immune response do actually induce bystander T cell activation.…”
mentioning
confidence: 99%
“…CD62L is usually expressed at a high level on resting T cells [36,37], while CD25, the α-chain of IL-2 receptor expressed upon T-cell activation, has been used as a marker for activated T cells [38][39][40]. The data showed CD62L+ Tcell population was reduced (and thus CD62L low population was increased) in PBMC from immunized mice.…”
Section: Discussionmentioning
confidence: 99%